2016
DOI: 10.5993/ajhb.40.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Comparing GPS, Log, Survey, and Accelerometry to Measure Physical Activity

Abstract: Objectives Both self-report and objective measures have strengths and limitations for studying physical activity (PA) and travel. We explored how objectively measured global positioning system (GPS) and accelerometer data matches with travel logs and questionnaires in predicting trip duration and PA. Methods In a study of PA and travel among residents in Atlanta, GA conducted in 2008–2009, 99 participants wore GPS devices and accelerometers, and recorded all trips in a log for 5 consecutive days. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
1
20
2
Order By: Relevance
“…As stated in the inclusion criteria, all studies used EMA methodology, meaning that participants were signalled to complete assessments throughout the course of the day at random or fixed times (time-based sampling) or when exhibiting certain behaviours (event-based sampling). In this review, fourteen studies (70%) used timebased sampling [37,39,49,55,57,58,60,62,63,66,67,72], two studies (10%) used event-based sampling [54,68] and four studies (4/20: 20%) used a combination of both [52,61,64,65]. The total monitoring period duration varied from 1 day to 6 months.…”
Section: Ema Methodsology Ema Sampling Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…As stated in the inclusion criteria, all studies used EMA methodology, meaning that participants were signalled to complete assessments throughout the course of the day at random or fixed times (time-based sampling) or when exhibiting certain behaviours (event-based sampling). In this review, fourteen studies (70%) used timebased sampling [37,39,49,55,57,58,60,62,63,66,67,72], two studies (10%) used event-based sampling [54,68] and four studies (4/20: 20%) used a combination of both [52,61,64,65]. The total monitoring period duration varied from 1 day to 6 months.…”
Section: Ema Methodsology Ema Sampling Approachmentioning
confidence: 99%
“…Event-based sampling Of the six studies that used event-based sampling or a combination of time-and event-based sampling, three (50%) used a deviceinitiated assessment, in which the device (handheld/ smartphone) initiated the assessments in response to a behaviour or event (2 GPS, 1 mobile phone's built-in motion sensor) [52,64,65]. The other three (3/6: 50%) used a self-initiated assessment in which participants were asked to self-initiate assessments in response to specific behaviours or event [19,54,61,68]. In one of these event-based studies (17%), it was not reported whether each event had to be assessed [65].…”
Section: Ema Methodsology Ema Sampling Approachmentioning
confidence: 99%
See 3 more Smart Citations